Penetapan Kadar Fenolik Total pada Fraksi n-Heksana, Etil Asetat, Air dan Ekstrak Daun Bayam Merah (Amarantus gangeticus Hort) dengan Metode Folin-Ciocalteu - FITRI PUJIATI; FRANSISKA LEVIANA (Fakultas Farmasi Universitas Setia Budi, 2012)
Red spinach leaves (Amarantus gangeticus Hort) is one of plant that contain phenolic compound which has benefit for human. The aim of this study was to determine total phenolic content on n-hexane, ethyl acetate, and water fractions of ethanolic extract of red spinach by Folin-Ciocalteu. Red spinach leaves were macerated by ethanol 70%, than were fractionated by of n-hexane, ethyl acetate, and water. Extract and fractions were analyzed the total phenolic content by Folin-Ciocalteu method. The study showed that total phenolic content of red spinach were (4,05%±0,175) GAE for ethanolic extract; (2,15%±0,045) GAE for n-hexane fraction, (11,03%±0,290) GAE for ethyl acetate fraction; (4,4%±0,180) GAE for water fraction.